The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7717/peerj.13112
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival among Hawaiian corals outplanted from tanks to an ocean nursery are driven by individual genotype and species differences rather than preconditioning to thermal stress

Abstract: The drastic decline in coral coverage has stimulated an interest in reef restoration, and various iterations of coral nurseries have been used to augment restoration strategies. Here we examine the growth of two species of Hawaiian Montipora that were maintained in mesocosms under either ambient or warmed annual bleaching conditions for two consecutive years prior to outplanting to determine whether preconditioning aided coral restoration efforts. Using coral trees to create a nearby ocean nursery, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…To date, findings supporting the effect of environmental priming regimes on coral thermal tolerance are equivocal. While most studies indicate that a "challenging" thermal history or preconditioning regime (of thermal variability or elevated baseline temperature) enhances thermal tolerance of corals (McClanahan et al 2005;Bellantuono et al 2012b;Palumbi et al 2014;Buerger et al 2015;Schoepf et al 2015;Kenkel and Matz 2016;DeMerlis et al 2022;Brown et al 2023), some report neutral or negative results, including cases where corals ended up less stress resistant compared to the control group (Putnam and Edmunds 2011;Camp et al 2016;Schoepf et al 2019;Henley et al 2022). It has been suggested that such preconditioning treatments must have exerted too much stress on the corals with the consequence of having drained their energy reserves, hence did not contribute to stresshardening but rather had a contrary effect (Hackerott et al 2021;Wong et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, findings supporting the effect of environmental priming regimes on coral thermal tolerance are equivocal. While most studies indicate that a "challenging" thermal history or preconditioning regime (of thermal variability or elevated baseline temperature) enhances thermal tolerance of corals (McClanahan et al 2005;Bellantuono et al 2012b;Palumbi et al 2014;Buerger et al 2015;Schoepf et al 2015;Kenkel and Matz 2016;DeMerlis et al 2022;Brown et al 2023), some report neutral or negative results, including cases where corals ended up less stress resistant compared to the control group (Putnam and Edmunds 2011;Camp et al 2016;Schoepf et al 2019;Henley et al 2022). It has been suggested that such preconditioning treatments must have exerted too much stress on the corals with the consequence of having drained their energy reserves, hence did not contribute to stresshardening but rather had a contrary effect (Hackerott et al 2021;Wong et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have reported positive effects of a variable environment on the stress tolerance in corals (Doering et al 2021;Oliver and Palumbi 2011b;Buerger et al 2015;Wong et al 2021;DeMerlis et al 2022;Brown et al 2023), a few have not reported any improvements or rather observed declines in stress tolerance. Negative reports are likely due to stress-buildup during the preconditioning process (Hackerott et al 2021), which can occur when a variability regime becomes too challenging (Putnam and Edmunds 2011;Camp et al 2016;Schoepf et al 2019;Klepac and Barshis 2020;Henley et al 2022). Also, dynamic interaction of all covariates present in the respective study sites can act as confounding factors and influence the outcomes of preconditioning (as laid out in the chapter above), but most importantly, the "priming dosage" will be decisive for the success of the method.…”
Section: Considerations For the Design Of Efficient Stress-hardening ...mentioning
confidence: 99%
“…Outplant sites can vary in their morphology (a at reef structure versus a spur and groove system) and the abiotic conditions they exhibit [27][28][29] . With different coral species exhibiting habitat preferences [30][31][32] , it is a key consideration for restoration. Additionally, within species variability also needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…There are several possible contributing factors that may provide greater coral holobiont resilience to bleaching events: host-and/or symbiont-species (29)(30)(31)(32), host genotype (33)(34)(35)(36)(37)(38), or the microbial constituents of the holobiont's microbiome (39,40). At the center of this complex equation is the host's metabolic capacity before and after bleaching (i.e., how is the coral acquiring nutrients to sustain growth and immune function?).…”
Section: Introductionmentioning
confidence: 99%